Analisis Genetika: Sebuah Catatan Singkat Mengenai Penerapannya pada Suku Cervidae (Rusa dan Kijang): Genetic Analysis: A Brief Note of Its Application on Family Cervidae (Deer and Muntjak) - Ivan Yusufi Noor; Erna Suzanna (Department of Forest Resources Conservation and Ecotourism - IPB University, 2009)
This papaer presents a bref note of genetically based studyof Cervidae. Many genetically based studies were performed on Cervids n last 20 years, and thidse are about many species, aspects and objectives. Most of these study using genetic analysis as the basic methods, and those objectives are : (1) to reveal genetic variability among populationa or individuals; to determine sex, individual, subspecies or species; to perform phylogenetic relationship and evolution and forensics. The importance of those kind of studies are reveal a variety of genetics informations that are relevant and usefull for population management and conservation. Using allof informations that are releaved from previous and recent study, it is possible to applying genetic analysis on Cervids of Indonesia. Genetics markers and methods that are necessary for these kind of study have been availbe, and the objectives of study, such as 5 species of deer and muntak of Indonesia, were ready to be explored. Keywords: Cervidae, Genetics Analysis, Genetic Markers, Objectives and Methods